Computer Modeling of Anterior Circulation Stroke: Proof of Concept in Cerebrovascular Occlusion - Phan, Thanh G.; Hilton, James; Beare, Richard; Srikanth, Velandai; Sinnott, Matthew (Frontiers in Neurology, 2014)
Background: Current literature emphasizes the role of the Circle of Willis (CoW) in salvaging ischemic brain tissue but not that of leptomeningeal anastomoses (LA). We developed a computational model of the cerebral circulation to 1) evaluate the roles of the CoW and LA in restoring flow to the superficial compartment of the middle cerebral artery territory and 2) estimate the size of the LA required to maintain flow above the critical ischemic threshold (>30% of baseline) under simulated occlusion. Methods: Cerebral vasculature was modelled as a network of junctions connected by cylindrical pipes. The experiments included occlusion of successive distal branches of the intracranial arteries while the diameters of LA were varied. Results: The model showed that the region of reduced flow became progressively smaller as the site of occlusion was moved from the large proximal to the smaller distal arteries. There was no improvement in flow in the MCA territory when the diameters of the inter-territorial LA were varied from 0.0625 mm to 0.5 mm while keeping the intra-territorial LA constant. By contrast, the diameter of the inter-territorial LA needed to be greater than 1.0 mm in order to provide adequate (>30%) flow to selected arteries in the occluded MCA territory. Conclusions: The CoW and inter-territorial LA together play important supportive roles in intracranial artery occlusion. Computational modelling provides the ability to experimentally investigate the effect of arterial occlusion on CoW and LA function.